1994
DOI: 10.1016/s0006-3495(94)80596-x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral diffusion measurement at high spatial resolution by scanning microphotolysis in a confocal microscope

Abstract: Fluorescence photobleaching methods have been widely used to study diffusion processes in the plasma membrane of single living cells and other membrane systems. Here we describe the application of a new photobleaching technique, scanning microphotolysis. Employing a recently developed extension module to a commercial confocal microscope, an intensive laser beam was switched on and off during scanning according to a user definable image mask. Thereby the location, geometry, and number of photolysed spots could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 12 publications
1
75
0
Order By: Relevance
“…At low counterion concentrations ( 10 mM), sample fluorescence was reduced, consistent with previous observations [21]. For all samples, analysis of the recovery series showed that the expected linear dependence of the second moment of the radial distribution of bleached fluorophore on time and recovery kinetics were consistent with first-order behaviour of a single component [12].…”
Section: Diffusion Measurements and Data Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…At low counterion concentrations ( 10 mM), sample fluorescence was reduced, consistent with previous observations [21]. For all samples, analysis of the recovery series showed that the expected linear dependence of the second moment of the radial distribution of bleached fluorophore on time and recovery kinetics were consistent with first-order behaviour of a single component [12].…”
Section: Diffusion Measurements and Data Analysissupporting
confidence: 89%
“…The confocal-FRAP instrumentation and variance recovery analysis, for determining self and tracer lateral-diffusion coefficients, was as previously described [8,12,13]. Lateral selfand tracer-diffusion coefficients were calculated from the timedependence of plots of the second moment of the radially averaged distribution of bleached fluorophores.…”
Section: Diffusion Measurements and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The intersection between the slope of the linear decreasing (anomalous diffusion regime) and the line corresponding to the final and constant value of the diffusion coefficient (normal diffusion in a dense medium) yields the crossover time between these two behaviours 56 . Although a confocal laser scanning microscope was used, the uniform circular disc profile approximation 38,[43][44]48 , described first in 1983 by Soumpasis 47 , is a suitable model to study our confocal FRAP curves. In fact, according to Pucadyil and…”
Section: Anomalous Diffusionmentioning
confidence: 99%
“…An important number of manuscripts explain how, from Axelrod et al equation 42 (Gaussian profile approximation) for stationary lasers, it is possible to study the diffusion of tracer particles (e.g. proteins) in 2D or 3D media when a confocal FRAP is employed [38][39][40][41][43][44][45][46]48 . But, normally, in 2D media confocal FRAP experimental curves can be examined using Soumpasis equation 47 (uniform circular disc profile approximation) for nonscanning microscope 48 .…”
Section: Introductionmentioning
confidence: 99%